sTREM2 cerebrospinal fluid levels are a potential biomarker in amyotrophic lateral sclerosis and associate with UMN burden - Jiao, Lin; Yang, Jing; Wang, Wenjing; Liu, Xiangyi; Fu, Yu; Fan, Dongsheng (Frontiers in Neurology, 2024)
ObjectivesThe aims of this study were to investigate whether CSF sTREM2 may be a potential marker of disease monitoring for amyotrophic lateral sclerosis (ALS).MethodsWe investigated whether CSF sTREM2 levels are altered in ALS patients and are correlated with upper motor neuron (UMN) burden and disease progression.ResultsCSF sTREM2 was greater in the ALS patients than in the controls (p = 0.002). Elevated CSF sTREM2 was associated with the UMN score (r = 0.38, p = 0.009), ΔFS (r = 0.30, p = 0.04) and serum NFL (lg) (r = 0.35, p = 0.015). As the motor band sign (MBS) score increased, the CSF sTREM2 level increased (p-trend = 0.014). Furthermore, the correlations became stronger (UMN score (r = 0.50, p = 0.01) ΔFRS (r = 0.52, p = 0.008) and serum NFL (lg) (r = 0.55, p = 0.004) when estimated only among patients with a disease duration >12 months.ConclusionWe found that CSF sTREM2 is elevated in ALS patients and may be a novel marker, probably reflecting upper motor unit severity and prognosis.